2022
DOI: 10.3390/cancers14041009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pVHL Interactome in Human Testis Using High-Throughput Library Screening

Abstract: Functional impairment of the von Hippel–Lindau tumor suppressor (pVHL) is causative of a familiar increased risk of developing cancer. As an E3 substrate recognition particle, pVHL marks the hypoxia inducible factor 1α (HIF-1α) for degradation in normoxic conditions, thus acting as a key regulator of both acute and chronic cell adaptation to hypoxia. The male mice model carrying VHL gene conditional knockout presents significant abnormalities in testis development paired with defects in spermatogenesis and inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The regulation of the transcriptional factor KAP1, also known as TRIM28 (a ubiquitin ligase), by SMURF2, another ubiquitin ligase, in breast cancer cells was shown by Shah et al [ 15 ]. Mutations of substrates binding motifs of VHL, a ubiquitin ligase adaptor that functions as an E3 substrate recognition protein, were reported by Faclconieri et al and found to be associated with VHL tumors [ 16 ]. The discovery of an inhibitor of the deubiquitinase OTUD7B by Chen and colleagues provides evidence for a potential therapeutic target in leukemia cells [ 17 ].…”
mentioning
confidence: 99%
“…The regulation of the transcriptional factor KAP1, also known as TRIM28 (a ubiquitin ligase), by SMURF2, another ubiquitin ligase, in breast cancer cells was shown by Shah et al [ 15 ]. Mutations of substrates binding motifs of VHL, a ubiquitin ligase adaptor that functions as an E3 substrate recognition protein, were reported by Faclconieri et al and found to be associated with VHL tumors [ 16 ]. The discovery of an inhibitor of the deubiquitinase OTUD7B by Chen and colleagues provides evidence for a potential therapeutic target in leukemia cells [ 17 ].…”
mentioning
confidence: 99%